Analysis of sediment variation and influencing factors in the upper Yangtze River in the past 50 years, China. Issue 5 (2nd May 2022) - Guo, Wenxian; Jiao, Xuyang; Huang, Lintong; Zhou, Haotong; Zhao, Ruichao; Wang, Hongxiang
Abstract: River sediment load has a profound impact on river geomorphology and river ecosystems. We selected sediment load data from 1965 to 2019 from three key hydrological stations in the upper reaches of the Yangtze River: Pingshan, Cuntan, and Yichang. We have used the Mann-Kendall method, t-test, and wavelet analysis to analyze the characteristics of sediment load variation, the Cumulative volume slope rate of change, and the River Impact method to quantitatively assess the degree of sediment variation and the influencing factors. The results show that (1) The annual sediment load at the upper reaches of the Yangtze River at the Pingshan, Cuntan, and Yichang stations all showed a significant decreasing trend, with mutations in 1997, 2003, and 2002, respectively, with the main period of 15 years, 24 years, and 10 years. (2) A series of human activities such as interception of dams, sand mining in river channels, and soil and water conservation measures are the main reasons for the significant reduction of sediment load in the upper reaches of the Yangtze River, with the contribution of human activities exceeding 80% in all cases after the 1990 s and 90% after the 21st century. (3) Under human activities, the annual sediment load at Cuntan station has been highly altered, while serious alterations have occurred at Pingshan and Yichang stations. The results of the study can provide a corresponding reference for ecological protection and restoration in the Yangtze River basin. HIGHLIGHTS: Analyzed the sediment variation in the upper Yangtze River in the past 50 years. Quantitatively evaluated the degree of sediment alteration. The contribution of climate change and human activities to sediment variation was quantitatively assessed. To discuss and analyze the influencing factors of sediment variation and the resulting environmental impact.